interdisciplinary performance-based approach to training laboratory animal technicians - Romick, M.L; Chavez, J; Bishop, B (Lab animal, 2006)
Experience has proven that comprehensive training and education make it easier to attract and retain highly qualified animal care technicians, as well as to ensure that research facilities reach maximum performance. The authors outline the training approach used at SoBran, Inc., by describing the subject matter covered in their initial orientation period and in ongoing training sessions. The authors also address recordkeeping methods and training-program assessment.